The Impact of (TPRS) Strategy on Improving ‎Language Vocabulary of Preschool Children ‎in Jordan - Abu Al-Rish ‎, Maha; Al-Mistareehi, Hussain (Jordan Journal of Educational Sciences, 2024)
The study aimed to identify the impact of the TPRS strategy in improving the vocabulary of preschool children In Jordan. A quasi-experimental design was used in this study. The study sample consisted of 39 boys and girls selected intentionly from Dafa Academy in Jordan,. They were chosen randomly divided into two groups. The experimental group had 21 boys and girls, while the control group included 18 boys and girls To achieve the objectives of the study, the researchers built a teacher's guide for implementing the TPRS strategy and building a vocabulary learning test, divided into three skills that represent skills for learning vocabulary. these include the semantic skill in terms of the type of relationship between the linguistic vocabulary, significance in terms of the type of vocabulary, and connotation in terms of meaning and proper linguistic use of the vocabulary. The results of the study showed that there was a difference in the vocabulary learning test, and in each of the three vocabulary learning skills. For the benefit of the experimental group, and there were no statistically significant differences in vocabulary learning due to the gender variable or the interaction between gender and strategy